The debye dielectric behavior of mixed normal and relaxor-ferroelectrics: Monte Carlo investigation - Yongyut Laosiritaworn (2018)
In this work, Monte Carlo simulation was used to investigate the Debye dielectric behavior of mixed normal- and relaxor-ferroelectrics. The results show that, with increasing temperature, the dielectric permittivity of the mixed system sharply increases at low temperatures but slowly decays at high temperatures, while still presenting the dielectric peaks close to the relaxor- and normal-ferroelectrics transition temperatures. Further, it is found that the sharpness, the magnitude, and the frequency dispersion of the dielectric peaks can be finely tuned by adjusting relevant normal-ferroelectric parameters in the model. However, the modified Curie-Weiss law shows that its exponent γ is governed by the inverse-temperature dependence as the exponent is very close to 2 regardless of normal-ferroelectric content. The functionalities of the Debye-type dielectric permittivity are then discussed along with the comparison with experiments. © Taylor & Francis Group, LLC.